(untitled) (Asian Journal of Social Science Studies, 2022)
Objective: To investigate the chain mediating effect of intolerance of uncertainty and proactive coping on the relationship between childhood trauma and anxiety among Chinese college students. Methods: 409 college students completed the Childhood Trauma Questionnaire, Self-rating Anxiety Scale, the Intolerance of Uncertainty Scale and Proactive Coping Inventory. Results: (1) The score of Proactive Coping Inventory was negatively correlated with those of Childhood Trauma Questionnaire and Self-rating Anxiety Scale, while the score of Intolerance of Uncertainty Scale was positively correlated with scores of Childhood Trauma Questionnaire and Self-rating Anxiety Scale. There is a positive correlation between Intolerance of Uncertainty and Proactive Coping; (2) Intolerability of uncertainty and proactive coping play a chain mediating role in the relationship between childhood trauma and anxiety of college students. Conclusion: In the cognitive and coping process of childhood trauma experiencer, intolerance of uncertainty and lack of proactive coping promote the severity of anxiety symptoms, but the chain path of childhood trauma → intolerance of uncertainty → proactive coping → anxiety is a negative mediator, indicating a certain protective mechanism.